Composing language - Russell, James S., 1911- (Macmillan, 1974)
"Composing Language" is a language program designed to increase the student's language skills in order to facilitate the transition between oral self-expression and original composition. The 15 soft-cover student worktexts contain color visual material, material from newspapers and magazines, and selections from drama and literature which present stimuli intended to encourage various types of self-expression including mime, oral language, and class composition. It also includes student response books for grades 3 through 8 which are designed to provide a structured format that will enable students to organize their experiences and perceptions into written form.